Konstruksi Invasi Rusia Ukraina dalam Pemberitaan Media Nasional: Analisis Framing Media Online JawaPos.com dan Tribun Pekanbaru.com Edisi Februari-Maret 2022 - Hamidah, Vinda (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
The media is a means of mediation that has an important role in influencing many people, therefore media bias can occur. Indeed, the media is in between social reality with all its conflicts, interests, and diverse facts. The existence of bias in the media cannot be separated from its ideology. Framing analysis is a text analysis method used to dissect the ways or ideology of the media when constructing a fact. This research aims to analyze the framing that occurs on two news portals, namely Jawa Pos and Tribun Pekanbaru, towards the invasion case that occurred between Russia and Ukraine. Both media have different biases by showing the delivery of vocabulary, quotes, and sentences that can be constructed with different facts. This descriptive qualitative research uses the framing analysis model of Zhongdan Pan and Gerald M. Kosicki. The differences in the news raised by Jawa Pos and Tribun Pekanbaru are visible in the sources, quotes, and sentences used so as to produce different constructions. Jawa Pos has its own characteristics in informing news related to the heating up of Russian and Ukrainian news, whereas Jawa Pos seems to display the strengths and support of the Ukrainian state. In contrast to Jawa Pos, Tribun Pekanbaru displays information related to the strength and defense possessed by Russia. Keywords: Media, Framing, Ideology, Invasion.